2012
DOI: 10.1155/2012/967347
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Treatment Using Peptides: Current Therapies and Future Prospects

Abstract: This paper discusses the role of peptides in cancer therapy with special emphasis on peptide drugs which are already approved and those in clinical trials. The potential of peptides in cancer treatment is evident from a variety of different strategies that are available to address the progression of tumor growth and propagation of the disease. Use of peptides that can directly target cancer cells without affecting normal cells (targeted therapy) is evolving as an alternate strategy to conventional chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
269
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(288 citation statements)
references
References 134 publications
0
269
0
3
Order By: Relevance
“…5,6 Chan et al 54 found that GNPs with diameters between 20-60 nm have the highest uptake in HeLa cells. Also, it was found that some peptides, known as cell-penetrating peptides (CPPs), can be uptaken specifically by certain cell organelles.…”
Section: Targeted Drug Delivery and Cellular Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Chan et al 54 found that GNPs with diameters between 20-60 nm have the highest uptake in HeLa cells. Also, it was found that some peptides, known as cell-penetrating peptides (CPPs), can be uptaken specifically by certain cell organelles.…”
Section: Targeted Drug Delivery and Cellular Uptakementioning
confidence: 99%
“…The peptides and proteins utilised in these systems can fulfil different roles, acting as drug carriers, anti-cancer drugs and even cellular targeting moieties. 5,6 In the last decade, a variety of peptide functionalized GNPs have been synthesized and applied in a range of areas including bio-detection, targeted drug delivery and cellular uptake studies. [7][8][9][10] Adding peptides to citrate-capped GNPs can produce highly stable peptide-capped nanoparticles even in an aqueous buffer.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used strategy for prostate cancer treatment is synthetic luteinizing hormone releasing hormone (LHRH) administration to inhibit androgen biosynthesis in the testes. This occurs via negative feedback when overexposure to LHRH causes lowered LHRH receptor expression, leading to decreased luteinizing hormone (LH) and follicle-stimulating hormone (FSH) secretion from the anterior pituitary gland, ultimately resulting in decreased androgen synthesis (47,48). Commercially available forms of LHRH antagonists include abarelix and degarelix (49,50).…”
Section: Utility and Limitations Of Peptide-based Therapymentioning
confidence: 99%
“…Classical peptide drugs like LHRH analogues have been conjugated with doxorubicin, a chemotherapeutic agent, which selectively targets cells overexpressing LHRH receptors (57,58). A corollary to peptide carriers are homing peptides, which are independent of tumor type and target specific molecules in either normal or diseased tissues (59, 60) Targeting angiogenesis may include targeting peptides including RGD and NGR peptides, which home in on a v integrin receptors and aminopeptidase N, respectively (48), which are overexpressed in the neovasculature surrounding the tumors (59). A major drawback of peptide-based drugs is bioavailability.…”
Section: Utility and Limitations Of Peptide-based Therapymentioning
confidence: 99%
“…Peptide research for neurodegenerative diseases has recently made considerable contribution similar to that of cancer (Thundimadathil 2012), type 2 diabetes mellitus (Pinelli and Hurren 2011;Kaspar and Reichert 2013) and cardiovascular diseases (Lorber 2013). The major focus of drug design against AD is the inhibition of amyloid beta (Ab) peptide aggregation (Sciarretta et al 2006;Wang et al 2014), the causative pathogenic process as supported and established by the Amyloid cascade hypothesis (Hardy and Higgins 1992).…”
Section: Introductionmentioning
confidence: 99%